2012
DOI: 10.1007/s00125-012-2529-x
|View full text |Cite
|
Sign up to set email alerts
|

Low serum 25-hydroxyvitamin D level predicts progression to type 2 diabetes in individuals with prediabetes but not with normal glucose tolerance

Abstract: Aims/hypothesis Vitamin D deficiency may increase the risk of type 2 diabetes. We therefore investigated whether serum concentrations of 25-hydroxyvitamin D [25(OH)D] would predict the development of prediabetes (impaired fasting glucose, impaired glucose tolerance or the two combined) and type 2 diabetes, either on their own or when combined with serum concentrations of IGF-1 or IGF-binding protein-1 (IGFBP-1), which may interact with 25(OH)D. Methods At baseline, participants aged 35-56 years without known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
3
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 34 publications
7
93
3
5
Order By: Relevance
“…We demonstrated in a Swedish cohort that low 25(OH)D levels were predicting type 2 diabetes risk over 10 years in subjects with prediabetes, but not with normal glucose tolerance at baseline (4). Recently, a meta-analysis confirmed this association (5).…”
Section: Serum 25-oh-vitamin D [25(oh)d]mentioning
confidence: 80%
“…We demonstrated in a Swedish cohort that low 25(OH)D levels were predicting type 2 diabetes risk over 10 years in subjects with prediabetes, but not with normal glucose tolerance at baseline (4). Recently, a meta-analysis confirmed this association (5).…”
Section: Serum 25-oh-vitamin D [25(oh)d]mentioning
confidence: 80%
“…12 The changing lifestyle, urbanization and modernization of Indian population has led to possible reduction of people being exposed to direct sunlight and inadequate intake of dietary vitamin D, thereby leaving the population at increased risk of vitamin D Deficiency and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies have reported that low vitamin D status is a predictor for incident type 2 diabetes (11,12). Still, it remains unclear whether vitamin D deficiency and insulin resistance are causally related or whether they constitute two independent features of patients with type 2 diabetes.…”
mentioning
confidence: 99%